INTEGRASI PEMANFAATAN RUMPUT GAMA UMAMI DAN PUPUK KOMPOS SEBAGAI UPAYA PENGUATAN PERTANIAN BERKELANJUTAN DALAM KERANGKA EKONOMI HIJAU DI DESA SEMBALUN BUMBUNG - Sennur, Bq Ajeng Okfly; Bachri, Diva Agatha; Saputri, Febi Aulia; Berlian, Berlian; Iqbal, Lalu Ahmad Kharil; Royani, Sani; Hambali, Rosi Fathul; Anjaningrum, Bening Salsabila Dwi; Dinda, Dwi Nur; Sakti, Muhammad Nune Huria; Rosmaliati, Rosmaliati (Jurnal Wicara, 2025)
This community service activity through the Village Community Empowerment Field Study Program (KKN-PMD) aims to initiate an integrated farming model through the use of Gama Umami grass and the introduction of compost fertilizer in Sembalun Bumbung Village. The background of the program is the limited availability of quality animal feed and high production costs due to dependence on chemical fertilizers. This program introduces Gama Umami grass as a superior feed source and compost fertilizer (a mixture of bio-slurry and mushroom straw waste) as an organic fertilizer innovation. The activities were carried out using a participatory approach at the end of the KKN-PMD period. The results of the activities show that the initial planting of Gama Umami grass and the application of compost fertilizer on carrot fields were successfully initiated as a pilot project. Although quantitative monitoring has not yet been carried out, this program has successfully demonstrated the potential of a circular agricultural system that can significantly reduce production costs by reducing the purchase of chemical fertilizers. This program recommends the importance of continued assistance for the sustainability of green agricultural practices.